Exotic Nations Literature and Cultural Identity in the United States and Brazil, 1830-1930 - Wasserman, Renata (Cornell University Press, 1994)
In this highly original and critically informed book, Renata R. Mautner Wasserman looks at how, during the first decades following political independence, writers in the United States and Brazil assimilated and subverted European images of an "exotic" New World to create new literatures that asserted cultural independence and defined national identity. Exotic Nations demonstrates that the language of exoticism thus became part of the New World's interpretation of its own history and natural environment.